Mobilidade e atividade cerebral de crianças e adolescentes com paralisia cerebral - Sudati, Isabella Pessóta (Universidade Federal de São Carlos, 2025)
In recent years, the incorporation of evidence-based practices has been strongly encouraged in the treatment of children and adolescents with cerebral palsy (CP). However, although mobility is a significant limitation for these individuals, interventions with this focus still lack studies that describe their effective components and mechanisms of action. This thesis aimed to contribute to this topic through three studies, synthesizing the available evidence on the effectiveness of mobility-focused interventions, as well as the relationships between neural reorganization and mobility in CP, and investigating the implementation of a mobility-focused intervention proposal. Study I summarized the neural correlates of mobility in children with CP found in the literature. The reviewed studies indicated that children with CP have increased brain activity and greater variability in cerebral reorganization during mobility activities and gross motor tasks compared to typically developing children. The review highlighted the importance of further studies investigating neural correlates during mobility activities to guide neurorehabilitation strategies aimed at supporting the implementation of effective intervention strategies for children with CP. Study II aimed to systematically review the available evidence on intensive mobility training in CP and determine the minimum effective dose to improve mobility. It was found that task-oriented training (TOT) can improve walking speed, endurance, and balance. Studies with homogeneous samples and outcomes are needed to support clinical recommendations for intensive mobility interventions and to clarify the minimum effective dose for these outcomes. Study III presented an innovative intervention proposal called Mobility Intensive Training (Mob-IT), which incorporated contemporary principles for promoting changes in mobility performance and explored mechanisms associated with change and preliminary effectiveness of the intervention in children and adolescents with CP through a single-subject design study, systematically describing the implementation of the training elements. After the intervention, clinically significant changes in mobility were observed through the TUG test, PEDI-CAT, walking speed and cadence, gross motor function, performance and satisfaction scores related to the intervention goals, which varied among individuals according to the trained goals, as well as a decrease in brain demand for task execution. To conclude, this thesis contributed a framework of evidence on mobility-focused interventions and demonstrated the mechanisms of neural reorganization and their impact on the mobility of children and adolescents with CP. Finally, it was possible to demonstrate that intensive mobility training can promote brain and biomechanical changes in mobility tasks, which facilitated understanding of the favorable intervention outcomes for each individual. Thus, the results provide elements to support the principles currently recommended for therapeutic interventions, promote their incorporation into clinical practice, and encourage ongoing research that may facilitate the implementation of evidence-based practices.
Mobility and brain activity of children and adolescents with cerebral palsy
Keywords: Fisioterapia; Crianças; Paralisia cerebral; Mobilidade; Atividade cerebral; Treino intensivo; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL